2018
DOI: 10.1589/jpts.30.320
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between agility and lower limb muscle strength, targeting university badminton players

Abstract: [Purpose] Targeting university badminton players, this study investigated the relationship between agility, which is associated with performance in badminton, and lower limb muscle strength, and examined which muscles influence agility. [Subjects and Methods] A total of 23 male university badminton players were evaluated for side-shuffle test scores and lower limb strength. The relationships between agility, lower limb strength, and duration of experience playing badminton were evaluated using a correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…Leone et al. (2014) also found agility problems among children with ALL who had been in complete remission for at least one-year, and Sonoda et al. (2018) found similar result and suggested that poor strength capacity may be its basis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Leone et al. (2014) also found agility problems among children with ALL who had been in complete remission for at least one-year, and Sonoda et al. (2018) found similar result and suggested that poor strength capacity may be its basis.…”
Section: Discussionmentioning
confidence: 68%
“…Motor problems, particularly fine motor and balance difficulties, among children being treated for ALL were later confirmed in a review publication (Green et al, 2013). Leone et al (2014) also found agility problems among children with ALL who had been in complete remission for at least one-year, and Sonoda et al (2018) found similar result and suggested that poor strength capacity may be its basis. In the present study, we found evidence for motor dysfunction that exceeded fine motor and balance skills to include difficulties with agility and muscle strength on the BOT 2-SF.…”
Section: Discussionmentioning
confidence: 82%
“…Successful performance in badminton requires players to accelerate, slow down, change direction, move fast and maintain balance (Girard & Millet, 2008; (Duncan, Chan, Clarke, Cox, & Smith, 2017). Change of speed is the ability to speed up and slow down at the same time as a change of direction (Sonoda, Tashiro, & Suzuki, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [8], for the complex environment, depth image technology is used for gesture recognition, and the average recognition rate of gesture can reach 98.4%. In racket motion recognition based on image and video data acquisition, [9] established an event hiding Markov model with binary classification according to the position of players on the court. Literature [10] proposed a badminton game data mining method based on two-dimensional sequence images.…”
Section: Introductionmentioning
confidence: 99%